Pemanfaatan Limbah Serai Wangi Sebagai Pakan Ternak dan Pupuk Organik di Desa Payakabung, Kabupaten Ogan Ilir, Sumatera Selatan - Fitra Gustiar; Munandar Munandar; Zaidan P. Negara; Efriandi Efriandi (Universitas Prof. Dr. Hazairin, SH, 2020)
Utilization of Citronella Waste as Animal Feed and Organic Fertilizer in Payakabung Village, Ogan Ilir Regency, South Sumatra Lemongrass is an essential plant that is easy to cultivate. Many farmers in Payakabung village cultivate it. There are 3 units of lemongrass essential refineries with a capacity of 2 tons per day, which produce 6 tons of citronella fragrant waste every day or 180 tons every month. The production of Citronella Waste is a problem in the area around the distillation plant, so a solution to this problem is needed. Utilization as animal feed and organic fertilizer is a solution that can be done, but the knowledge of farmers about the technology of utilizing citronella waste is still low, so it is necessary to carry out farmer assistance activities regarding the use of citronella waste as feed and organic fertilizer. activities carried out include coordination with the village government, training, discussion and evaluation. The results of this activity show the lack of knowledge of farmers about the use of citronella waste, the use of which is only done as mulch in rubber gardens. this activity increases the knowledge of farmers to use other citronella waste. This activity is expected to have an impact on reducing the citronella waste that has accumulated in Payakabung village.